GE_GERICHTE P/6703/2012 vom 10. Dezember 2013 - GE Cour de justice (2013)
ADMINISTRATION DES PREUVES; APPEL(CPP); VOL(DROIT PÉNAL); BRIGANDAGE; FIXATION DE LA PEINE; TORT MORAL; HONORAIRES; AVOCAT | CPP.389; CP.139; CP.172ter; CP.140; CP.47; CO.47; CPP.433